A cross-firm analysis of corporate governance compliance and performance in Indonesia. Issue 5 (28th February 2020) - Tanjung, Miranda
Abstract : Purpose: The study aims to construct a cross-firm corporate governance index to predict firm performance. The index consists of 15 governance elements from a large sample of the Indonesian firms covering the period from 2003 to 2013. Design/methodology/approach: This study presents robust results as the findings are tested by applying the generalized method of moments (GMM) estimator to eliminate endogeneity problems and unobservable heterogeneity posed by the relationship between performance and firm-level governance practices. Findings: The results indicate that the corporate governance index is associated with enhanced corporate financial performance. Likewise, the findings reported under the pooled ordinary least squares and GMM also indicate corporate governance sub-indexes (elements), which have significant effects on performance: whistleblower mechanism, audit quality, board of director size and blockholders. Research limitations/implications: In the emerging market context, this study supports the notion that active and self-regulated governance practices are appreciated by the market and, in the end, can have a positive impact on financial performance. The analysis adds to the empirical literature by providing insights into how governance provisions are being actively implemented in the micro level. With regard to weak governance practices, this study is consistent with previous studies, according to which, firms have the opportunity to use corporate governance as a way of differentiating themselves from other players in countries with poorly regulated investor protection and institutional settings. Originality/value: This study makes a positive contribution, as it looks at the impact of Indonesia's corporate governance compliance on the basis of a set of 15 unique governance provisions, including the findings of the positive influence of corporate governance in family business.